In vitro embryo production through modification of time and gonadotropin hormone during oocytes maturation - Triwulaninngsih, Endang; Toelihere, M.R; Rutledge, J.J; Yusuf, T.L; Purwantara, B; Diwyanto, K (Indonesian Animal Sciences Society, 2001)
This research has been conducted at the laboratory of in vitro fertilization of the University of Wisconsin, USA. These embryos can be used for improving genetic value of Indonesian cattle. There is transportation constraint in importing oocytes from USA. It takes more than 24 hours to bring it to Indonesia. In fact, oocytes maturation and ready to be fertilized normally requires only 24 hours in 5% CO2 incubator at 38.5°C. Therefore, this research is needed to study the effect of gonadotropin hormone and time for oocyte maturity and ready to be fertilized at a period more than 24 hours. If this problem could be solved then the importation of oocytes could be cheaper and easier than importation of life animals or embryos. Ovaries were collected from slaughterhouse in Wisconsin. Oocytes were matured in TCM-199 medium in 5% CO2 incubator and at 30°C enriched with FSH 10 μl/ml, oestradiol 17 β 1μl/ml and 10 % FCS as control of gonadotropin hormone treatment (A); with FSH 10 μl/ml (B); with oestradiol 17 β 1μl/ml (C) and without gonadotropin hormone (D) for 24 hours, 30 hours and 36 hours as time of maturation treatment I, II and III respectively. The oocytes were fertilized in vitro with motile sperm selection by Percoll gradient and incubation between sperm and oocytes in fertilization media (TALP) for 20 hours. All zygotes were cultured in modification of KSOM medium up to blastocyst and were fed serum 5 μl/50 μl medium on day 6. Data were analyzed by SAS program. Percentage of cleavage between time of maturation were significant (p<0.01); between gonadotropin hormone treatment A vs B and A vs C and B vs C and B vs D and between A vs D were significant (p<0.01), but between treatment C vs D were not significant (p>0.05). Percentage of blastocyst between time of maturation were not significant (p>0.05), but between gonadotropin hormone treatment A vs B and A vs C and B vs D and C vs D were significant (p<0.01), but between treatment A vs D and B vs C were not significant (p>0.05). Percentage of cleavage, morula, blastocyst, expanded blastocyst and unertilized ova on this study are 66.73%, 22.43%, 40.33%, 0.81% and 32.51 for 24 hours incubation (I); 61.55%, 25.69%, 32.69%, 0.54% and 27.61% for 30 hours incubation (II); 72.43%, 32.06%, 37.97%, 0.0% and 25.31% for 36 hours incubation (III) respectively. According to this study, in vitro production of embryo could be conducted at 30°C and incubation on maturation media for more than 24 hours. Key words: Oocytes, cleavage, embryos, blastocyst